Study on heavy metals biosorption ability of Saccharomyces cerevisiae - B, Thippeswamy; C.K., Shivakumar; M, Krishnappa (International Journal of Biological Research, 2014)
Potential Saccharomyces cerevisiae was isolated from paper effluent for bioremediation of heavy metals. Morphological studies, physiological tests and molecular characterization confirmed isolated yeast colony was S. cerevisiae. S. cerevisiae has showed high biosorption of Cd2 + (67%), followed by Pb2+ (61%)> Ni2+ (64%)> Cr6+ (63%)> Cu2+ (57%)> Zn2+ (53%). SEM image of heavy metals treated S. cerevisiae showed patches of accumulated heavy metals and ED’s spectrum of S. cerevisiae treated with heavy metals contained metal peaks. Elemental analysis by EDS confirmed that ion exchange mainly involved in heavy metals biosorption by S. cerevisiae. Optimization of parameters made maximum biosorption of heavy metals. The pH 4.0-5.0, temperature 20-25°C and contact time of 60 minute was found optimal for heavy metals biosorption. The metal biosorption was found maximum in single metal system compared to multi metal ions. Pre-treatment method enhanced the metal biosorption. Sorption isotherm studies fit into the model of Langmuir isotherm compared to Freundlich isotherm. Keywords: Biosorption, Heavy metals, Optimization, Saccharomyces cerevisiae, Sorption isotherm.